(untitled) (Bangladesh Critical Care Journal, 2023)
Traditionally known as a nosocomial organism and preponderance to infect the immunocompromised patients or with preexisting structural damage in lung parenchyma1, Burkholderia cepacia infection in an apparently immunocompetent host in ICU settings is not very commonly heard of. On the other hand, acute colonic pseudo-obstruction (Ogilvie’s syndrome) is also a very rare surgical complication. Here we present a case of a postpartum lady who developed colonic perforation following caesarean section due to Ogilvie’s syndrome and Burkholderia cepacia sepsis and eventually expired. Bangladesh Crit Care J March 2023; 11 (1): 43-45